2014
DOI: 10.1155/2014/185068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorophyll-Derived Efflux Pump Inhibitor Pheophorbideaand Pyropheophorbideaon Growth and Macrolide Antibiotic Resistance of Indicator and Anaerobic Swine Manure Bacteria

Abstract: Natural plant compounds, such as the chlorophyll a catabolites pheophorbide a (php) and pyropheophorbide a (pyp), are potentially active in the gastrointestinal tracts and manure of livestock as antimicrobial resistance-modifying agents through inhibition of bacterial efflux pumps. To investigate whether php, a known efflux pump inhibitor, and pyp influence bacterial resistance, we determined their long-term effects on the MICs of erythromycin for reference strains of clinically relevant indicator bacteria wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 111 publications
(175 reference statements)
0
12
0
Order By: Relevance
“…This hypothesis is consistent with our observation that the midgut preferentially binds chlorophyllide over chlorophyll. Tetrapyrrole molecules are known to bind a variety of proteins and to inhibit their functions (Miller and Shaklai, 1999;Golovina et al, 2013;Kraatz et al, 2014). For example, pheophorbide a is an inhibitor of the enzyme, cholesterol acyltransferase (Song et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is consistent with our observation that the midgut preferentially binds chlorophyllide over chlorophyll. Tetrapyrrole molecules are known to bind a variety of proteins and to inhibit their functions (Miller and Shaklai, 1999;Golovina et al, 2013;Kraatz et al, 2014). For example, pheophorbide a is an inhibitor of the enzyme, cholesterol acyltransferase (Song et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive compounds in fraction 3 of Surian leaves responsible for antibacterial activity against acne bacteria were pheophorbide a, pheophytin a and dihomo-γ-linolenic acid (Table 4). Kraatz et al (2014) reported that pheophorbide a could inhibit the growth of S. aureus and E. coli that are resistant to erythromycin and showed MIC of 50 μg/mL. Gomes et al (2015) also found that antibacterial activity of pheophytin, isolated from Sidastrum micranthum, was capable to suppress the growth of S. aureus, S. epidermidis, and E. coli with MIC of 75 μg/mL.…”
Section: Discussionmentioning
confidence: 97%
“…PhA has low solubility and permeability, and, as a Bcrp substrate, is poorly absorbed, which was reflected in PhA being detected in the intestine of PhA-gavaged mice, but was undetectable in the serum of WT mice gavaged with PhA. PhA has been reported to be mainly cleared unabsorbed in feces (Kraatz et al, 2014). Interestingly, we routinely found that ex vivo fluorescence comparison of the intestinal segments of WT mice fed a normal PhA-containing diet, after flushing out the intestinal contents, revealed a lower PhA fluorescence in the duodenum compared with a higher PhA fluorescence in the jejunum and ileum.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal assay for Bcrp activity would use a specific, inexpensive, fluorescent near-infrared (NIR) substrate probe that could be monitored in real time both in vitro (high-throughput) and in vivo. PhA is a breakdown product of chlorophyll and is a specific dietary substrate of Bcrp (Jonker et al, 2002;Robey et al, 2004;Kraatz et al, 2014), with an efflux ratio of 3.15 in cell lines overexpressing Bcrp (Zhang et al, 2009). Two laboratories have developed in vitro assays for BCRP function/inhibition using PhA, also showing that PhA is not a substrate for P-glycoprotein or MRP1 in vitro (Robey et al, 2004(Robey et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%